Decrypting the sediment record of very late stage volcanic activities in Tatun volcano group, Northern Taiwan: evidence from ashy deposits - Guo-Teng Hong; Damià Benet; Kuo-Lung Wang; Fidel Costa; Liang-Chi Wang (Terrestrial, Atmospheric and Oceanic Sciences)
Abstract The Tatun Volcano Group (TVG) is an active volcano on Taiwan and poses a potential threat to public safety in northern Taiwan. Currently, the youngest eruption records among the TVG occurred around Mt. Chihsing in the late Pleistocene. One of these significant records is from the ashy layers exposed in a lacustrine sediment profile near Mt. Shamao. This study analyzes the mineralogy, petrography, ash componentry, and particle morphology of the ashy layers to characterize the volcanic activity at the TVG, including eruption behavior and style. A previous study inferred that phreatic eruptions occurred near Mt. Chihsing between 17 − 13 ka using radiocarbon dating on finely dispersed organic materials in the neighboring horizons of the ashy layers (Belousov et al. 2010). Based on the evidence of sediment components, petrographic texture, particle morphology, hydrothermal mineral phases, and co-depositional diatoms, this study argues that the ash in question is not an in-situ tephra deposit and proposes two possibilities for its origin: (1) resedimented volcaniclastic deposits from hydrothermal products in a volcanic epithermal environment, not implying any eruption activity; or (2) volcanogenic sedimentary deposits formed by either syn-eruptive or post-eruptive floods. Based on the inconsistent acidity ranges revealed by the mineral assemblages in the ashy samples, the post-eruptive origin is favored, i.e. volcanogenic sedimentary deposits formed by reworked tephra from multiple events. The eruption ages of their tephra sources are unmeasurably older than the radiocarbon age obtained from the current deposits, which are not indicative of volcanic eruption ages.